(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research is important because of the importance of the subject matter and the implications for the future of development in Iraq. This requires linking the accounting systems with the economic developments. The accounting system we will address in this research is the cost accounting system and its role in determining value added tax. The value added tax and the extent of the relationship with the general accounting principles of cost accounting through which the value added is determined provided the use of a sound and effective cost system. The problem of research was about knowing the role of cost accounting in determining the value added tax and whether following the accounting systems properly and effectively will lead to a proper report on VAT for goods and services. The researchers found a number of results, To VAT should take into account the general accounting principles, especially cost accounting. This means that the failure to use an effective and sound cost system will affect the calculation of value added tax fairly, and the failure to observe the laws and tax regulations and accounting systems and Lack of bookkeeping and accounting records leads to difficulty in accessing the value of change in value added and thus VAT cannot be calculated. In order to ensure the proper identification of the Value Added Tax (VAT) of goods and services, a sound and effective accounting system must be followed. The application of accounting systems and principles should also be applied, and the role of accountants and accountants should be regulated to regulate the accounting profession. In order to properly determine VAT.